Jade-Carving Chisel and Luminous Ocean : Selected Essays by Jao Tsung-i on Literature and Related Topics - Williams, Nicholas Morrow, (Asian Studies E-Books Online, Collection 2025., 2025)
Jao Tsung-i's scholarship illuminated the development of classical Chinese literature from antiquity through the end of the Qing dynasty. In this volume, eight interviews with and essays by Jao are translated faithfully into English, giving a sampling of his diverse insights into literature and its broader significance. Topics range from the religious beliefs underpinning the earliest Chinese writings, to the influence of Chan Buddhism on Chinese poetics, to Gu Yanwu's (1613-1682) poetic protest against the Manchu conquest. Collectively the essays demonstrate how literary art and spiritual beliefs have been intertwined throughout Chinese history.